Analysis of the Content of the Chemistry Book for the Third Intermediate Stage According to Environmental Problems - et. al., Dia Mahdi Hussein, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current aim of this study is to know Environmental problems which included in the content of chemistry textbook of intermediate third stage : -To achieve this aim, the researcher organized a listing of environmental issues consisting of (8) major areas, namely (air and air pollution, water pollution, soil pollution, energy, disturbance of biodiversity and environmental balance, waste management foods and medication pollution, mineral wealth investment). Of which (60) sub-issues, then the researcher analyzed the chemistry book for the third intermediate stage for the academic year (2020-2021) in slight of the listing that was prepared, its validity and validity. The consistency of the book became confirmed, and the effects confirmed that the chemistry textbook for the 0.33 grade had a mean of (15) sub-issues, and a percent of ( 25%). In slight of the studies effects, the researcher recommends consisting of the content of the chemistry textbook for the third intermediate stage and the major and minor environmental issues that aren't available, as one of the current developments in medical education.